Increasing Women Senior Managers Effectivness: Evidence from Romania - Farhad Analoui (Romanian Journal of European Affairs)
In the wider context of increased participation of women to managerial positions, the issue of effectiveness at work has become equally important for female managers. Therefore it is important to identify the factors, which can determine an increase in their managerial effectiveness. This article looks at the factors conducive to managerial effectiveness in organizations, as perceived by women senior managers in Romania. The research was carried out through questionnaires and semi-structured interviews applied to a sample group of 35 Romanian women managers at various levels, in both public and private institutions. The empirical results were then analysed with theoretic instruments. The main conclusion of the research was that, for Romanian female managers, work effectiveness is determined primarily by the managerial skills and knowledge acquired by women. These in turn are connected with the years of accumulated work experience, seniority, and education, especially if it is centred on managerial education.